"I think you did it!": Examining the effect of presuming guilt on the verbal output of innocent suspects during brief interviews. Issue 3 (19th August 2019) - Portnoy, Shiri; Hope, Lorraine; Vrij, Aldert; Granhag, Pär‐Anders; Ask, Karl; Eddy, Carly; Landström, Sara
Abstract: Innocent suspects interviewed by a guilt‐presumptive versus innocence‐presumptive or neutral interviewer may tend more to display non‐verbal behaviours which neutral judges consider indicative of guilt. We examined the effects of interviewer's presumption of guilt on innocent mock suspects' alibis. Participants ( N = 90) provided an alibi to convince an interviewer of their innocence of a theft after she implied that she believed that they were guilty or innocent or that she had no belief about their veracity. On the basis of existing conflicting findings for suspects' verbal behaviour during accusatory interviews, we predicted that alibis in the guilt‐belief condition would contain the highest or lowest number of correct details with overall higher or poorer accuracy rates, respectively. Although participants perceived the interviewer's presumptive approach, the number of correct details provided and accuracy rates of alibis did not differ significantly between conditions. We propose explanations to these findings and future research paths.